KONSEP BIOPHILIC DESIGN DALAM ARSITEKTUR KONTEMPORER: TINJAUAN TEORETIS - Fariz Nizar; Aufannuha Ihsani; Dwipa Gunadharma; Alfian Faza P.; Dias Wahyu Rifai; Siti Roudhotul M. (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
The development of contemporary architecture presents challenges to environmental sustainability and human psychological needs for connection with nature. The concept of biophilic design emerged as a response to these conditions, by integrating natural elements into the built environment to improve the well-being and comfort of users. This study aims to review and reformulate the concept of biophilic design in contemporary architecture through theoretical studies, emphasizing the importance of integrating the basic principles of biophilia that are in-depth, cross-disciplinary, and relevant to the modern urban context. The method used is a literature study through analysis of literature from various relevant sources, including journals, books, and architectural case studies. The results of the study show that the application of biophilic design principles, such as the use of natural light, vegetation, cross-ventilation, and natural forms, can improve the quality of space and have a positive impact on the psychology and productivity of occupants. By integrating biophilia principles ​​into modern building design, biophilic design not only contributes to aesthetics, but also to the sustainability and health of the built environment.